ANALISIS PENGARUH RASIO PROFITABILITAS TERHADAP PERTUMBUHAN LABA PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIAPERIODE 2018 – 2022 - Winner Aan Suranta Putra Ginting; Dini Asrianti (Adisam Publisher, 2024)
This study uses independent variables, namely return on assets and return on equity with the dependent variable, namely profit growth. The object of research is on banking companies listed on the Indonesia Stock Exchange for the period 2018-2022. The sample selection was carried out using purposive sampling technique and obtained a sample of 7 companies. The objectives of this study are: Test and analyze the eflect of return on assets on profit growth in banking companies listed on the Indonesia Stock Exchange for the period 2018 – 2022. After conducting research using with the multiple linear analysis methods, it can be concluded: 1. Return on assets has no eflect on profit growth in banking companies for the period 2018-2022. 2. Return on equity has no eflect on profit growth in banking companies for the period 2018-2022. 3. Return on assets and return on equity together have an eflect on profit growth in banking companies for the period 2018-2022.